Childhood neglect and intimate partner violence: the mediating role of the dark triad - Dudka, Katarzyna (2019)
Childhood neglect is the most prevalent form of child maltreatment. The outcomes of being neglected as a child are often more serious than that of abuse. Nonetheless, research on this topic is currently limited. The present study examined the mediational properties of the dark triad personality traits on the relationship between history of neglect and the perpetration of intimate partner violence. The data was collected from 465 participants, who were recruited online. Once participants agreed to take part in the study, they could complete the questionnaires. At the end of the study, they were presented with a debrief with phone numbers to domestic violence helplines. Participants completed three questionnaires regarding (1) their experiences in childhood, (2) their personality characteristics and (3) behaviours in a romantic relationship. It has been found that neglect did not significantly predict if a person perpetrates intimate partner violence. On the other hand, antisocial traits were a significant predictor of violent behaviour in romantic relationships for females but not for males. The mediation analyses demonstrated that there is no direct effect between neglect and perpetration of intimate partner violence, but there is an indirect effect for women only. The findings indicate that antisocial traits are an important factor for establishing if individuals neglected in childhood perpetrate violence in their intimate relationship. Therefore, it is important that future research takes this into consideration to find effective intervention programmes to reduce the rate of re-offending.